2007
DOI: 10.1063/1.2740107
|View full text |Cite
|
Sign up to set email alerts
|

“Blueshift” in photoluminescence and photovoltaic spectroscopy of the ion-milling formed n-on-p HgCdTe photodiodes

Abstract: Photoluminescence characterization of n-on-p Hg1−xCdxTe photodiodes formed by ion-milling technique shows that the luminescence peak of the n-type conversion region shifts remarkably toward higher energy with an amount of ∼40meV more than that of the p region. The photovoltaic response of the diodes was examined. The origin of the “blueshift” may be ascribed to the Burstein-Moss effect associated with the high electron concentration of the type conversion region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
3
16
0
Order By: Relevance
“…Even a higher value (~7´10 16 cm -3 ) was reported for the n−type converted region of ion− −milled MCT MWIR photodiodes [13]. This value was ob− tained with laser beam induced current measurements, and was in a good agreement with results of the photolumi− nescence (PL) study, which showed the PL peak of the n−type converted region blue−shifted by~40 meV in respect to the p−region.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Even a higher value (~7´10 16 cm -3 ) was reported for the n−type converted region of ion− −milled MCT MWIR photodiodes [13]. This value was ob− tained with laser beam induced current measurements, and was in a good agreement with results of the photolumi− nescence (PL) study, which showed the PL peak of the n−type converted region blue−shifted by~40 meV in respect to the p−region.…”
Section: Discussionsupporting
confidence: 79%
“…The other exception was MWIR MBE films, where the n 77 (f) was (4−7.2)×10 15 cm -3 . It is important that n 77 (f) in un−doped samples was much higher than the n 77 in the as−grown samples (the latter constituted~10 13 cm -3 in the MWIR films and~10 14 cm -3 in the LWIR films). This testifies to the fact that some of the as−grown samples were heavily compensated.…”
Section: Discussionmentioning
confidence: 96%
“…The physical picture is illustrated with the schematic band diagram in Fig.2. Finally, we would like to point out that the position dependent luminescence is unlikely due to the composition nonuniformity of HgCdTe material, because the blueshift was observed to be 39 meV, much larger than non-uniformity related energy uncertainty of approximately 6 meV (or ~ 50 cm -1 ) as revealed by photoluminescence on different locations as well as by photovoltaic spectroscopy on different diodes of the same monolith material [2]. Such a BM effect-associated phenomenon is significant to device design of the ion milling-based diodes fabrication of HgCdTe.…”
Section: Resultsmentioning
confidence: 95%
“…Many new phenomena and the underlying physics are still under exploration. In our recent researches on ion-milling formed n-on-p diodes of HgCdTe [2], it was noted that the cutoff response of devices shifted generally to higher energy aspect of the absorption edge of the monolith material as measured by transmission spectroscopy. Such a blue shift is an unexpected and unwanted results for device application.…”
Section: Introductionmentioning
confidence: 98%
“…26 Meanwhile, optical absorption and PL measurements indicated an energy level of V Hg to be about 9~12 meV above the valence-band maximum of HgCdTe. 27,28 The values were contradictory, and the second level of V Hg was not experimentally observed though it was theoretically predicted to be a double-level acceptor. 24 Our recent PR study of As-doped HgCdTe shows that impurity related process is detectable by PR spectroscopy 13,15 and impurity levels can be estimated by temperature-dependent PR measurements.…”
Section: Impurity Levels In As-doped Hgcdtementioning
confidence: 93%